HAK KEKAYAAN INTELEKTUAL ARTIFICIAL INTELLIGENCE : URGENSI REFORMASI HUKUM NASIONAL - Abu Darda’ Al Faruq; Dara Puspitasari; Sylvia Setjoatmadja (Dinamika Hukum & Masyarakat, 2026)
The development of Artificial Intelligence (AI) poses crucial challenges in theIndonesian Intellectual Property Rights (IPR) regime with two main problemformulations: 1) How does the current Indonesian positive legal regulationregulate works or inventions produced by Artificial Intelligence and is there anormative vacuum regarding the recognition of Artificial Intelligence as a creatoror inventor in the IPR regime? 2) How do the applicable legal provisions regulatethe ownership and protection of Intellectual Property Rights over works orinventions produced through automated processes by Artificial Intelligence, and towhat extent do these provisions provide legal certainty? This normative juridicalresearch uses a statutory, conceptual, and comparative approach to Copyright LawNo. 28 of 2014 and Patent Law No. 13 of 2016, finding that positive law limitscreators/inventors to humans only (Pasal 1 paragraph 9 of the HC Law, Pasal 4letter d of the Patent Law) thus making AI a legal object rather than a subject,creating a normative vacuum such as the global DABUS case where IPR ownershipdepends on human contributions without the certainty of a fully automated process.It is recommended that AI-specific legislation reform based on ethics beimplemented in the Minister of Communication and Information TechnologyCircular Letter No. 9 of 2023 for Indonesia's adaptive protection.Keywords: Artificial Intelligence, Intellectual Property Rights, AI Inventors, IPRNorm Void, Legal Certainty